Acidentes de trânsito com vítimas na faixa etária pediátrica: aspectos epidemiológicos e clínicos - Freitas, Juliana Pontes Pinto (2006)
Nowadays, traffic injuries and violence are important causes of health problems to children population. With the objective to know epidemiologic and clinic aspects of the traffic accidents involving children admitted in large public hospital in Uberlândia MG, it has been done a descriptive case series research analyzing, retrospectively, medical records of children younger than 15 years old, who were admitted to the Hospital das Clínicas de Uberlândia (HCU), from January 1999 to December 2003. Within the results it can be marked that the victims average age was eight years old and 65.7% were boys; 76.6% were cyclists or pedestrians; 7.1% of the pedestrians were admitted at intensive care unit and 2.6% died; 58.8% of the passengers of motorcycles and of four or more wheels vehicles were not using security devices properly. The occurrence of pre-hospital assistance before admission at HCU was identified in 33.1% patients; 44.5% patients were admitted at the hospital with a time interval smaller than one hour; 45.9% suffered traumatic brain injury, 6.8% severe and out of these 64.8% were admitted at intensive care unit. 61.0% of the cyclists suffered isolated limb lesions and 57.5% pedestrians suffered multiple lesions; 83.3% of the surgeries included orthopedic procedures; 9.0% stayed at the hospital for more than two weeks. Of the deaths 66.7% were pedestrians and 78.6% occurred within 48 hours after admission and in 85.7% traumatic brain injury occurred. In conclusion, the victims are, in average, eight years old and are mainly boys. The vehicle most frequently involved in accidents is the bicycle and the ones with pedestrians are commonly more severe. When passengers, frequently are not using security devices properly. Many victims received pre-hospital assistance in other heath units before being transferred to HCU and are admitted in this hospital after the first hour of the accident. The assistance given by fireman was not associated with longer survival. Commonly the children victims of traffic accidents suffer lesions in limbs, brain or multiple; the occurrence and severity of the traumatic brain injury determines the evolution; surgeries are mainly orthopedic procedures; around 10% stayed at the hospital for more than two weeks and death is more frequently among pedestrians.